2017
DOI: 10.1186/s41239-017-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Situated learning through intergenerational play between older adults and undergraduates

Abstract: This study is grounded in a social-cultural framework that embeds learning in social activities, mediated by cultural tools and occurring through guided participation in the social practice of a particular community. It uses conversation analysis as a tool to examine the structures of the talk-in-interaction of naturally occurring conversations between 11 pairs of older adult (aged between 65 and 92) and undergraduates (aged between 18 and 25) during a 6-week social practice of intergenerational digital gamepl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
(44 reference statements)
1
23
0
Order By: Relevance
“…Importantly, we found that, when games were presented in a cultural context (as an artistic medium) the interest in games transcended the cliché expectations of cognitive stimulation, distraction and physical therapy. Our work provides additional support for the importance of an intergenerational approach to game research by tackling the issue from the perspectives of increasing inclusion and diversity, through the processes of co-design (Vanden Abeele and De Schutter 2010; Kaufman et al 2017;Derboven et al 2011), situated learning and increasing social interaction by co-playing among different age groups (Zhang et al 2017;Chua et al 2013). For review of previous work, see (Costa and Veloso 2016;Zhang and Kaufman 2016b;de la Hera et al 2017).…”
Section: Significance Of the Studymentioning
confidence: 55%
See 1 more Smart Citation
“…Importantly, we found that, when games were presented in a cultural context (as an artistic medium) the interest in games transcended the cliché expectations of cognitive stimulation, distraction and physical therapy. Our work provides additional support for the importance of an intergenerational approach to game research by tackling the issue from the perspectives of increasing inclusion and diversity, through the processes of co-design (Vanden Abeele and De Schutter 2010; Kaufman et al 2017;Derboven et al 2011), situated learning and increasing social interaction by co-playing among different age groups (Zhang et al 2017;Chua et al 2013). For review of previous work, see (Costa and Veloso 2016;Zhang and Kaufman 2016b;de la Hera et al 2017).…”
Section: Significance Of the Studymentioning
confidence: 55%
“…In this study, instead of focusing on a single game, or a genre of games, we provided a space for exploring different possibilities of using games as modes of communication and invited older participants to critique whether games could be pertinent to their lifestyle. This approach is different from previous multi-session studies like Zhang et al (2017), in that we used the context of healthcare applications of serious games as a point of departure to understand the cultural relevance of serious games in a safe space without expectations to learn, perform or adopt any one particular game.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Along with Kolb’s (1984) experiential learning theory, many scholars (e.g., Beard & Wilson, 2002; Dirkx, 2001; Merriam, Caffarella, & Baumgartner, 2007) emphasized the importance of emotion in experiential learning because “the affective domain can be seen to provide the underlying foundation for all learning” (Beard & Wilson, 2002, p. 119). Several qualitative studies employed this theory to describe older adults’ particular learning experiences in which they went from adopting mobile devices to further utilizing mobile devices as their informal learning medium (Lindsay et al, 2007; Zhang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For some team members in our study, the lack of relevant technical skill or prior gaming experience created feelings of incompetence. Although the more skilled team members were keen to offer their help (Reich et al 2013;Zhang et al 2017), we observed that those with higher technical aptitude and experience in computer games occasionally ended up leading the others, who simply followed their instructions (on, for example, which button to press on the keyboard) rather than developing a deeper understanding of the team assignment and taking pleasure in discovering solutions for themselves.…”
Section: Pedagogical Implicationsmentioning
confidence: 77%